Faktor yang Berhubungan dengan Hiperemesis Gravidarum di Puskesmas Puskesmas Birem Bayuem Aceh Timur Tahun 2024 - Sumiati Sumiati; Ester Simanullang; Febriana Sari (Inovasi Kesehatan Global, 2025)
Maternal Mortality Rate (MMR) is a component of the development index and quality of life index which is calculated by taking into account and considering women's health status (MMR). The aim of this research is to determine the factors associated with hyperemesis gravidarum at the Birem Bayuem Community Health Center in 2024. The design of this research is an analytical survey using a cross-sectional approach. The sample in this study was all 1st trimester pregnant women who visited ANC at the Birem Bayuem Community Health Center in 2024, namely 26 pregnant women. The results of the analysis using the Telst Chi-sqularel test showed a value of p=0.008 (95% CI 1.522-26.081). Mothers who are working have a rate of 6,300 times more likely to experience hyperreleasing disease compared to mothers who are not working. It is hoped that by increasing the number of antenatal care, follow-up or maternal visits in research will reduce the number of cases of hyperelelmosis. Apart from that, it is highly recommended that you learn about health regularly by actively asking health professionals every time you visit a health care facility.